The association between neck and shoulder discomfort–Katakori–and high somatizing tendency. Issue 1 (2nd January 2020) - Fujimoto, Yoh; Fujii, Tomoko; Oshima, Yasushi; Oka, Hiroyuki; Tanaka, Sakae; Matsudaira, Ko
Abstract: Objectives: 'Katakori', discomfort or dull pain around the neck and shoulder, is common in Japan. Somatizing tendency is important in the quality of daily living. This study aimed to examine the association between disability due to Katakori and high somatizing tendency. Methods: This internet study included 34, 754 Japanese adults who reported Katakori in the past four weeks. Katakori was classified into four grades: 1) no Katakori, 2) Katakori without difficulty in activities for daily living (ADL), 3) Katakori with ADL difficulty but without absence from social activities, and 4) Katakori with absence from social activities. Somatizing tendency was assessed using the Somatic Symptom Scale-8 (SSS-8). The association between a very high (SSS-8 ≥ 16) somatizing tendency and Katakori grade was examined using logistic regression adjusting for age, sex, body mass index, marital status, smoking, regular exercise, low back pain, depression, and the number of chronic conditions. Results: Katakori grade was significantly associated with a very high somatizing tendency (Odds ratio (OR)= 5.36 [4.36–6.60] in grade 4 vs. 2, and OR= 2.57 [2.30–2.89] in grade 3 vs. 2). Conclusion: When treating severe Katakori with disability, somatizing tendency should be assessed to facilitate better management.